(Re)definiranje prava varstva osebnih podatkov v luči razvoja umetne inteligence - Strle, Nadja (Pravni letopis, 2025)
This article situates itself within the ongoing social and legal discourse on the development of artificial intelligence models trained on data sources that typically include detailed information about individuals - their private lives, interests, and beliefs - and, in particular, on user data from social media platforms. It focuses on the question of the lawful legal basis for such processing, examining the purported legal ground of legitimate interests through a case study of Meta. The question of whether such processing is permissible under the General Data Protection Regulation has been live since Meta announced its intention to process user data for this purpose, with complaints from individuals, non-governmental organisations, and supervisory authorities leading to a postponement of the planned processing. Notwithstanding the disputed legal basis, Meta commenced the use of user data from Facebook and Instagram on 27 May 2025. The author illustrates the legitimate interest test with reference to Meta’s processing activities, drawing on the criteria outlined in European Data Protection Board Opinion No. 28/2024 on certain aspects of personal data processing in the context of artificial intelligence models, as well as relevant case law of the Court of Justice of the EU. The article aims to shed light on the flexibility of the legal basis of legitimate interest and to move beyond a generalised understanding that prioritises consent as the primary legal ground. The General Data Protection Regulation does not establish a hierarchy among legal bases; each possesses specific advantages and limitations. Ensuring the consistent and coherent application of EU data protection law across Member States is therefore essential. In this context, the article examines which criteria of the legitimate interest test still lack sufficient precision to facilitate a harmonised approach by the European supervisory authorities.